APPLYING A CUSTOMER RELATIONSHIP MANAGEMENT (CRM) SYSTEM FOR CLINIC MEDISTIRA 2 - Pramitha Dwi Larasati; Ari Irawan; Nikmatul Hikmah (Universitas Tridharma, 2020)
The clinic is a small-scale medical facility that only serves outpatient care for specific complaints.Medistira 2 is a clinic in the Cicadas Gunung Putri built to support the Cicadas village environment's healthaspects. In its operational activities, Medistira 2 has encountered problems related to information services topatients. There was a queue of patients accumulated at the time of registration and during treatment, making thepatient anxious and uncomfortable. There is no management of responses to criticisms and suggestions of theMedistira 2 submitted by patients (who can be called customers). Therefore, to create high customer loyalty, itis necessary to manage good relationships to not switch to other outpatient clinics. The management is done bycreating a Customer Relationship Management (CRM) system to determine the CRM's CRM effect on customerloyalty at Medistira 2. Data collection methods in this study are interviews, observations, and questionnaires.The system development method used is Prototype by doing Blackbox-testing as a system test. The resultsobtained indicate that the application of CRM to the Customer Loyalty factor is acceptable or significant(complimentary). Keywords—Patient, Clinic, Customer Relationship Management (CRM)